Meanings of nursing care for the family of patients in palliative care - Marcos Paulo de Oliveira Lima; Mônica Cordeiro Ximenes de Oliveira (Rev Rene)
Objective: to understand the meaning of nursing care for the family of patients in palliative care. Methods: field, descriptive, and exploratory study with qualitative approach conducted in secondary general hospital in the State of Ceará, Brazil. The participants comprised eight family members of patients in palliative care, with the conduction of semi-structured interviews and direct observation. For data analysis, we used the thematic category analysis. Results: data revealed the construction of three thematic categories. The meaning of nursing care for the family of patients in palliative care is anchored in the physical presence of these professionals, the performance of technical procedures, and teamwork. Conclusions: we verified that the nursing care highlighted by families aims at a humanistic care, established in the presence and based on human interaction.